PERKEMBANGAN HOTEL SYARIâ€™AH DI INDONESIA; MENGONSEP PARIWISATA ISLAMI - Ali Sabri, Fahruddin (KARSA Journal of Social and Islamic Culture, 2012)
Fahruddin Ali Sabri (Penulis, dosen STAIN Pamekasan, Jl. Raya Panglegur Km. 04 Pamekasan. Kontak 08521346464, e-mail didin021@yahoo.com) Â Â Abstract Indonesian tourism sector has been developed rapidly and significantly. Hotels sector high income contribution indicates the significant development, so it influences public prosperity. Syariâ€™ah Hotel is one of the hotel models offering certain facilities that matches Islamic values.Â ItsÂ development opens promising market chance that must be grounded on non-alcohol, drug-abused free and adultery prohibition concept. It facilitates the guests to have comfortable and safe stay. Kata-kata kunci Hotel, Pariwisata dan SyarÃ®â€™ah